PERAN STRUKTUR MODAL, ROA, DAN QUICK RATIO DALAM MEMENGARUHI HARGA SAHAM DAN NILAI PERUSAHAAN PADA BANK UMUM YANG TERDAFTAR DI BEI PERIODE 2020-2023 - Rahmawati, Rike; Sari, Lita Permata; Minullah, Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Commercial banks support economic growth by financing various sectors such as industry, trade, and investment. This study aims to determine the effect of Capital Structure, ROA, and Quick Ratio on Company Value through Stock Price as an intervening variable in Commercial Banks Listed on the IDX for the 2020-2023 period. The population in this study was Commercial Banks Listed on the IDX for the 2020-2023 period. The sampling technique was determined by purposive sampling. This study’s data analysis and hypothesis testing used the Smart PLS 3.0 application. The direct effect hypothesis test results showed that Capital Structure, ROA, and Quick Ratio had a significant effect on Stock Price and an insignificant effect on Company Value. Stock Price had a significant effect on Company Value. Capital structure, ROA, and Quick Ratio do not significantly affect Company Value through Stock Price.